Current strategies of the brachial plexus palsy management - Tokarzewska, Agata; Korga, Mateusz; Kowalczyk, Adrian; Małyska, Justyna; Tybulczuk, Balbina; Sikora, Katarzyna; Baj, Jacek (Journal of Education, Health and Sport, 2023)
The importance of brachial plexus palsy treatment is associated with its significant severity, along with Brachial plexus palsies can be treated by means of many different surgical and non-surgical methods which allow regeneration of full efficiency of the affected limb. The choice of method depends on such factors as type and region of injury, patient’s age or clinical presentation of the injury. The purpose of this review is to present current strategies of treating brachial plexus palsies, depending on therapeutic needs of the particular patient. This is a review study based upon selective literature overview, with emphasis on works published within past 13 years. 6 separate methods of brachial plexus palsy were assessed, without distinction of the reason of palsy occurring. Some of the invasive methods include operative treatment performed directly on occupied nervous tissue, such as microneural plexus reconstruction and nerve transfers (lower subscapular nerve transfer and contralateral C7 nerve transfer) whilst the others revolve around restoration of function of affected neighboring structures by themselves, e.g. shoulder tendon transfers. Rehabilitation and botulinum toxin-based treatment are non-operative methods revolving around enhancement of the function of the affected upper limb. Main measure of effectiveness of the treatment is assessment of the range of motion of the affected limb (ROM). There is still not enough information available regarding long-term efficiency of microneural plexus reconstruction and botulinum toxin-based treatment. They require further investigation while other methods are used commonly.